Papel dos pequenos mamíferos não-voadores na dispersão de sementes em canga - MARIA FERNANDA REGIOLLI GODOI (2024)
Animal-mediated seed dispersal plays a crucial role in promoting natural regeneration in degraded areas, allowing seeds to reach the soil, establishing seed banks, connecting fragments, and facilitating the recolonization of native species at a lower cost and maintenance time. Seed dispersal by non-volant small mammals (NVSM) is mainly performed by marsupials and rodents. However, in mountaintop environments, such as ironstone outcrops (canga), endozoochory by mammals is poorly understood. The study aimed to investigate Seed Dispersal Effectiveness (SDE) compounds by NVSM and its role in the regeneration of degraded canga ecosystems impacted by mining. We conducted mammal surveys in degraded (DCA) and preserved (PCA) canga areas in the Serra do Gandarela National Park, southeastern Brazil, collected their feces, conducted germination experiments, and set up diaspore removal stations to assess how vertebrate exclusion affects seed removal. We recorded 13 species of wild mammals (DCA = 10, PCA = 10), seven medium and large-sized species (DCA = 4, PCA = 7), six NVSM species (DCA = 6, PCA = 3), and three invasive domestic species in the natural environment. Of the 61 fecal samples collected for NVSM, only three contained seeds of a single plant species (Miconia oligochaeta). The germinability index for gut passed seeds of Calomys tener was 0%, while for Monodelphis domestica, it was 3.6%, and for the control treatment, it was 11.2%. There was no statistically significant difference between the time to the first germination and the mean germination time for gut passed seeds of M. domestica and control. For the diaspore removal experiment, there was no difference between the vertebrate access and vertebrate exclusion treatments in any environment (degraded and preserved) or season (rainy and dry). Although non-volant small mammals (PMNV) perform various functions in the ecosystem, they have not been efficient seed dispersers in canga ecosystems regarding the qualitative aspect of seed dispersal effectiveness (SDE). However, it is necessary to expand sampling, including replicates of degraded and preserved areas, to enhance conservation and restoration efforts.